Transporte de material particulado em suspensão na foz do Rio Amazonas - SILVA, Heriton Kevin do Nascimento (2018)
The Amazon river daily contributes to Atlantic Ocean water and high amounts of suspended particulate matter (SPM), this transport of fine particles undergoes seasonal variation and along the tide. The first is a result of two distinct periods, differentiated as the rate of precipitation periods dry and rainy and the second variation is the encounter between river and marine forcings. In this sense the present work was general objective to quantify the seasonal and along the tidal difference in the transport of SPM, the north and south channels, the mouth of the Amazon River. For this there were two campaigns in each channel, one in November 2012 (dry season) and another in June 2013 (rainy season) in both spring tide. Each channel was fragmented into left bank stations, right margin and a half in order to verify the spatial distribution of the investigated properties for each station collected to surface water and bottom over five sections distributed over a tidal cycle, the record the tide oscillation was acquired with a pressure sensor and flow data were generated by application of a numerical model with a hydrodynamic simulation package D-flow were also made turbidity records to be analyzed qualitatively, so that if corroboration with the SPM data. Quantification of SPM was performed by gravimetry and the calculation of its transport was considered that the SPM moved concomitantly with the water flow. During the rainy season, it was observed an SPM transport on average 4.5 higher compared to the opposite period, which obtained an average transport between channels of 33,259 (toneladas.estágío-1). Explained by the widening of the river and its tributaries during the rainy season which causes particulate inclusion in its flow and is best observed in areas affected by deforestation, another response to this increase is the intensification of erosion in the Andean regions that add to particulate carreado by River. The south channel showed the highest rate in the transport of SPM to the Atlantic Ocean, about 50% higher for both periods in response to morphological configuration of the environment, given that the greater fluid intake is given by this channel. Throughout tide SPM transportation presented, where higher values during ebb stage, giving the SPM exported as environment due to tidal asymmetry, where time ebb and flood time greater than. Turbidity and records SPM concentrations also had an increase during the rainy season and showed increase in their rates with depth, justified by the interaction between the water discharge with unconsolidated substrate.